ANALISIS KELELAHAN AXLE SHAFT TRUK ISUZU ELF 125 Ps - Rifanli Wahab; Stenly Tangkuman; Tritiya A Rante Arungpadang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2017)
Axle Shaft or wheel driver shaft is a component of a vehicle that intended to continue the rotation of the differential to the wheels. The purpose of this research is to get the distribution of life, damage, and safety factor on the axle shaft due to fatigue load using Ansys 14 software, and to know the location at the axle shaft that potentially damaged due to fatigue load. At first, literature study was undertaken, then did data colecction. After that, developed model of Axle Shaft using SolidWorks 2013. Finally, did fatigue analysis with software Ansys Workbench 2014. Based on the analysis, obtained life time, damage, and safety factor at Axle Shaft. In addition, also did macroscopic observations at surface of a broken Axle Shaft. Distribution value of life time, safety factor, and damage due to fatigue loads have been obtained. On the other hand, the location at axle shaft that most potentially damaged is about 3.3 cm from the left end. Based on the macroscopic observation, the damaged at Axle Shaft cause by torsion occurring at the shaft. Keyword: Fatigue, Axle Shaft, Simulation